CREATIVITY IN EFL CLASSES: EXAMINING TURKISH SECONDARY SCHOOL TEACHERS’ ATTITUDES AND THOUGHTS - Çelik, Vildan; Akyıldız, Seçil Tümen (My University, 2021)
The study aimed to investigate Turkish in-service EFL teachers’ attitudes towards creativity, to determine whether gender, age, teaching experience and undergraduate area of study influence their attitudes, and to examine their overall thoughts about creativity. The study used explanatory sequential design which is a mixed-methods research design. 200 EFL teachers participated in the quantitative whereas 20 teachers attended the qualitative part of the study. The quantitative data analysis was performed using SPSS 21 while NVivo 8 software was utilized for the qualitative data. The results revealed that most of the teachers exhibit positive attitudes towards creativity. There are, however, some points about which some teachers are not well-informed and have limited knowledge or misconceptions, as understood from their thoughts on the concept of creativity, creative teacher characteristics, and creative activities. Furthermore, several factors constrain their creativity and creative teaching practices. They agree on the need for teacher training to enhance creativity effectively in EFL. It was also determined that EFL teachers’ gender, age, teaching experience and undergraduate area of study do not influence their attitudes towards creativity.
Keywords: Eğitim; Eğitim Araştırmaları